The effect of ambiguity tolerance on learning English with computer-mediated dictionaries. Issue 8 (1st November 2020) - Chang, You-Hsuan
Abstract: In foreign language learning, computer-mediated dictionaries are among the most popular tools, and ambiguity tolerance (AT) is a key impact factor. However, few studies have focused on the effects of AT on computer-mediated dictionary-assisted English learning. To fill this gap, the current study explored the differences between two groups (a high AT group with 20 participants, and a low AT group with 21 participants) in learning processes (time spent on learning and dictionary usage) and learning performance (vocabulary acquisition and reading comprehension) during computer-mediated dictionary-assisted English learning. The correlation between AT and another important variable in dictionary-assisted learning, vocabulary size, was also explored. The results showed that low AT learners had better performance in reading comprehension, even though low AT learners and high AT learners had similar learning processes and performance in vocabulary acquisition. In addition, there was no correlation between AT during English learning and vocabulary size. This study may be of importance in explaining the unique role AT plays in learning English with computer-mediated dictionary assistance. Finally, the current article proposes suggestions for future studies and discusses implications for foreign language teaching and learning.